Comparison of Standard and Transepithelial Corneal Cross-Linking for the Treatment of Keratoconus: A Meta-analysis - Yu Di; Jingyi Wang; Ying Li; Yang Jiang (Journal of Ophthalmology)
Purpose. To compare the clinical results of standard corneal cross-linking (SCXL) with transepithelial corneal cross-linking (TECXL) in progressive keratoconus using a meta-analysis. Methods. PubMed, EMBASE, and Cochrane Central Register of Controlled Trials were searched up to June 2020 to identify relevant studies. The PRISMA guidelines were followed. Primary outcomes were change in uncorrected distance visual acuity and maximum keratometry (Kmax) after CXL. Secondary outcomes were change in corrected distance visual acuity, mean refractive spherical equivalent (MRSE), spherical and cylindrical error, endothelial cells density (ECD), and central corneal thickness (CCT). Results. Sixteen studies with a total of 690 eyes (SCXL: 332 eyes; TECXL: 358 eyes) were included. At the last follow-up, SCXL provided a greater decrease in maximum keratometry (Kmax) than TECXL (weighted mean difference (WMD) −1.12; 95% confidence interval (CI) −1.96, −0.29). For the other outcomes, there were no statistically significant differences. Conclusions. Except for a greater decrease in Kmax with SCXL group, both groups have a comparable effect on visual, pachymetric, and endothelial parameters at 24 months after surgery. Larger studies with a longer follow-up time are necessary to determine whether these techniques are comparable in the long term.